2018
DOI: 10.11648/j.ijhpebs.20180401.11
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Hepatitis B Surface Antigen Among Students of Medical Laboratory Sciences in Port Sudan Ahlia College

Abstract: Hepatitis B virus infection is a salient occupational hazard for health workers. It has been estimated that about two billion people worldwide have been infected with the virus. It is the 10 th leading cause of death worldwide and results in 500,000 to 1.2 million deaths per year due to cirrhosis and hepatocellular carcinoma. The presence of HBsAg in serum or plasma is an indication of active Hepatitis B infection, either acute or chronic. Healthcare workers, of which medical students are a part of, are at hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
0
0
1
Order By: Relevance
“…In a similar work carried out by Zakka et al 9 , a lower prevalence rate of 8.9% was recorded among blood donors in Gombe-Nigeria 9 . In another study conducted among Makere Medical students, an overall prevalence of 11.0% was recorded for HBsAg, which was slightly higher compared to the 10.5% prevalence recorded in this study, which is also higher than the result of a study obtained in Port Sudan Ahlia College among student as reported by Osman et al 10 According to Omatola et al 11 , WHO has established low prevalence as <2% and moderate prevalence as 2-8% and high incidence rate of >8% HBsAg positivity. It can then be deduced that the population screened in this study is highly prevalent with 10.5% reported.…”
Section: Discussioncontrasting
confidence: 84%
“…In a similar work carried out by Zakka et al 9 , a lower prevalence rate of 8.9% was recorded among blood donors in Gombe-Nigeria 9 . In another study conducted among Makere Medical students, an overall prevalence of 11.0% was recorded for HBsAg, which was slightly higher compared to the 10.5% prevalence recorded in this study, which is also higher than the result of a study obtained in Port Sudan Ahlia College among student as reported by Osman et al 10 According to Omatola et al 11 , WHO has established low prevalence as <2% and moderate prevalence as 2-8% and high incidence rate of >8% HBsAg positivity. It can then be deduced that the population screened in this study is highly prevalent with 10.5% reported.…”
Section: Discussioncontrasting
confidence: 84%